Health, Food Consumption, Social Economy, and Stunting Incidency in Timor Leste - Cipriano do Rosario Pacheco; Intje Picauly; Mindo Sinaga (KEMAS: Jurnal Kesehatan Masyarakat)
Stunting can affect the health of toddlers. The prevalence of stunting in Timor Leste in 2014 is 50.2%, whereas in Aileu District is 52.3%. Stunting can interfere intellectual growth and development. The purpose of this study was to analyze the relationship between stunting determinants. The research design was cross sectional. The population of this study was toddlers 24-59 months old, with a sample size of 102 people. Sampling technique used was simple random sampling. Data were analyzed bivariately using simple linear regression, while multivariate analysis was performed using multiple logistic regressions. Bivariate analysis revealed variables that have significant relationship with stunting: immunization (p=0.026), infectious disease (p=0.049), income (p=0.003), total family member (p=0.045). Multivariate analysis obtained two variables as determinant factor of stunting: infectious disease (p=0.025; OR=0.355; 95% CI=0.144-0.877), income (p=0.028; OR=0.332; 95% CI=0.124-0.887). The incidence of stunting in toddlers in Aileu District is very serious (54.9%). Toddlers with stunting demonstrated the adverse effects of stunting on growth, development, and the quality of human resources. Stunting is not only a health sector issue. It is necessary to have appropriate interventions with early and liable management through various related sectors.